Peresapan Antimikroba dan Antidiare pada Penderita Diare Akut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Background: Prescription given to patients must be rational. Prescibe knowledge can influence the rationality of presciption. This study was aimed to know the difference in rational prescribing, observing it from selection of medicine and diagnosis, between dysentery and diarrhea written by doctors and paramedics and to know the difference in rational prescribing of acute diarrhea, observing it from selection of medicine and diagnosis, between prescriptions written by doctors and paramedics. Methods: This was a retrospective study. Data were collected from medical record of acute diarrhea patients in 3 public Heath Centers of Bantu! Regency in 2000. Subjects were selected by cluster random sampling. Data collected including age, diagnosis (diarrhea or dysentry), prescibe, and kinds of medicine prescibed subjects were grouped in rational and irrational prescribing. Data were analyzed using Chi-square test. Results: this study finding is 1282 patients consisted of 27,61% dysentry and 72,39% diarrhea. From all of them, 42,04% and 57,90% were given the prescription by doctors and by paramedics respectively. Threre were 86,02% of dysentery and 33,69% of diarrhea patiens given rational prescribing by paramedics and 94,64% of dysentry and 38,13% of diarrhea patiens given the rational prescribing by doctors. From all of subject, 65,49% and 40,24% given rational prescribing by doctors and by paramedics respectively. Statistic test obtained both the significant difference of rational prescribing beetween dysentery and diarrhea written by doctors and paramedics (p